Interaction and language use in monolingual and multilingual preschool language environments - Larsson, Karolina (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
Many factors influence the language environment in preschool, for example, the language background and competence of the teachers, children's ages, language proficiency levels and language backgrounds, the access to play and learning materials and the composition of preschool groups. There is a lack of knowledge on how various aspects of the interactive language environment in preschool relate to children’s language use and language learning. The present thesis includes studies on various aspects of teachers’ and children’s interactional practices. The aim of the thesis is to highlight variation in reschoolers’ and teachers’ interaction and language use in monolingual and multilingual preschools in Sweden. The following research questions have guided the analysis: What characterizes children's and teachers’ verbal and embodied interaction and language use in preschools with monolingual and multilingual children? How do teachers’ and children’s interaction and language use contribute to the preschool language environment, and what does this signify for multilingual children's opportunities to acquire the language of education? The study builds on video ethnographic data. Teachers and children from eight preschool units situated in both high SES monolingual areas and low SES multilingual areas participate. Data was collected during nine months, and each group of teachers and children were video recorded during ordinary preschool activities such as play, mealtimes, teaching and storybook-reading. The video recorded data was transcribed and analyzed drawing on Conversation Analysis. As a complement to the video data, the participating children’s language production and language comprehension were assessed using The New Reynell Developmental Language Scales (Swedish version) and nonsense words. For paper 3 and 4, the transcriptions were also analyzed linguistically regarding word types, word tokens and decontextualized turns. The findings show that children use code-switching and crossing as interactional resources. Children are multilingual policy agents who create their own social and linguistic norms through multilingual practices, and they sometimes choose an alternative language as lingua franca in preschool (in this case English). Children’s play in both areas are characterized by interaction, joy, community, and joint attention, which create rich and stimulating social environments. However, children’s use of vocabulary differs between the areas, including both qualitative aspects (e.g. the use of decontextualized turns), and quantitative aspects (e.g. word types used). The vocabulary which children expose each other to during peer play talk is shaped and conditioned by their knowledge of the preschool lingua franca, in this case Swedish. L2 children in the multilingual preschools lack access to play with L1 speakers of the language of education, and their peer play talk is restricted by a joint low proficiency in Swedish. L1 children in monolingual preschools lack access to play with multilingual peer models. When children are allowed to take initiatives and act on their topics of interest during language teaching sessions, opportunities for concept development, abstract thinking, and cooperation arise. The preschool language teaching practices need to be dynamic and flexible in relation to children’s language backgrounds and their use of various language resources. A challenge arises when teachers and children have limited access to a lingua franca during language teaching. However, it is the role of the teacher to use a rich and varied language and to act responsively, and both follow and extend children’s contributions. Teacher's use of SSS might contribute to a language conducive context for children with special needs, but there is a risk that teachers’ focus on performance of SSS might constrain their responsivity. Teachers’ use of SSS therefore needs to be related to fundamental aspects of high-quality language interaction. The study concludes that children make strategic choices regarding which language to use in different contexts. All children have the right to participate, not only in socially rich and engaging play, but also in language conducive play where they can use and develop the curricular target languages. Teachers need to verbally support and enrich the play of children who are unable to act as sources of rich input to each other. Such support includes the use of a rich and diverse lexicon, advanced grammar and decontextualized language. Training preschool teachers how to improve their responsively oriented interactions with children might be a productive way of promoting the language learning environment of both monolingual and multilingual preschools.
Keywords: Preschool; Interaction; Peer interaction; Peer play talk; Children’s language choices; Children’s language use; Teachers’ interaction; Teachers’ language use; Language teaching; Teacher responsivity; Multilingualism; Monolingualism; Preschool language environments; Children’s use of English; Children’s agency; Children’s participation; Sign-supported speech; SSS; Lexical diversity; Equality in preschool